Does the intramuscular injection of vitamin D increase insulin resistance? - Bijan Iraj; Ashraf Aminorroaya; Massoud Amini (Wolters Kluwer Medknow Publications, 2012)
Objective: Considering the physiologic roles of vitamin D on insulin regulation, the effects of vitamin D treatment on insulin sensitivity and resistance indexes and beta cell function in pre-diabetic vitamin D deficient patients were investigated. Methods: In a randomized open clinical trial, 61 pre-diabetic vitamin D deficient patients who were the first degree relatives of type 2 diabetic patients, were enrolled and randomized into three groups (A, B and C). Group A (n = 21) were treated with intramuscular injection of 300,000 units of vitamin D at the beginning of the study and one month later. In group B (n = 20), injection of vitamin D plus 500 mg/d calcium and in group C (n = 20), just calcium was administered for two months. At baseline and two months later, oral glucose tolerance test was done. Homeostasis Model of Assessment-Insulin Resistance (HOMA-IR), insulin resistance index, Homeostasis Model of Assessment-B (HOMA-B) which is a beta cell function index, and Matsuda index, an insulin sensitivity index, were calculated and compared before and after intervention and between three groups. Findings: In vitamin D treated groups (A + B), the mean (SD) of HOMA-IR increased from 2.46 (1.36) to 3.1 (2.3) (P = 0.02), and Matsuda index decreased from 11 (3) to 9.0 (2.3) (P = 0.001). Conclusion: Injection of vitamin D increased insulin resistance and decreased insulin sensitivity indexes.